Análise transiente paramétrica de sistema poste-defensa devido ao choque de veículos - Queiroz, Janiel Silva de (2011)
It is known that is inevitable the incidence of traffic accidents in highways, where hundreds of thousands of vehicles pass daily. These accidents can cause material damages, physical and moral injuries to involved persons, besides fatalities. When collisions are into an electric distribution pole, these are responsible by five thousand residences without electric power immediately. In this case, the stop in supplying can take four hours to residents who live close to accident site due to replacement work, as well as to generating high costs to replace the poles. So, it is necessary to study a system that protects the pole, as well as safeguards the vehicles drivers in case of collision. The objective of this work is to evaluate the behavior of pole and of system pole-defence due to the vehicles shock. Two parametric analyses are carried out. The first one is the numerical modal analysis in order to determine the influence of components like cables and defence in the pole natural parameters. The second one is the transient parametric analysis of pole and of pole-defence system. In this case, the vehicle mass and his impact time are varied. These analyses are executed in the commercial program based on the Finite Elements Method, SAP2000 V.14.0. The displacement history of pole free end is compared between the several models, as well as with the results obtained when the dynamic load maximum value is applied statically. From results it is noticed that defence carries out his paper reducing the possibility of collapse due to increasing the natural frequencies and making away from excitation frequencies of impact loads. From transient analysis it is concluded that defence raises the rigidity of the system by reducing the displacements.